Parental involvement and Chinese elementary students' achievement goals: the moderating role of parenting style. Issue 3 (27th May 2018) - Zong, Xiaoli; Zhang, Lifan; Yao, Meilin
Abstract: Past research has revealed direct effects of parental involvement and parenting style on children's achievement goals separately, however, it is necessary to investigate the interactive mechanism in an integrated way. This study examined the relations between children's perception of different dimensions of parental involvement (i.e. home-based involvement, school-based involvement and academic socialisation) and their achievement goals, and the moderating role of parenting style (i.e. parental autonomy support vs. psychological control). Participants were 614 Chinese fourth and fifth grades students. Results showed that home-based involvement was positively associated with performance-approach goals, school-based involvement was positively associated with mastery goals, and academic socialisation was positively associated with both mastery and performance-approach goals. Parental psychological control moderated the relationships between performance-approach goals and two types of parental involvement: Academic socialisation and home-based involvement. These findings underscored the need of taking a multidimensional approach in conceptualising parental involvement, and that parental involvement should be expressed in an appropriate context of parenting style.